The Different Realization of Discourse Analysis in Translating Dentisty Abstracts into Arabic - Mohammed Nihad Ahmed (PROSPECTIVE RESEARCHES, 2023)
This study is directed towards the analysis of dentistry discourse, applied to the published paper abstracts with their translations. The study pointed out the discoursal functions projected in the paper abstracts that are rendered into the TL; it spotlights the randomly selected data that contains structural patterns in their contextual domains. Throughout the representation of the multifarious elaboration of the discourses, the study noted several issues under discussion. The nature of this study is descriptive rather than prescriptive in terms of the translation issues and what the translator has to do in rendering the dentistry discourse. The study concluded that the dentistry discourse, which is written for academic purposes, has a property of being direct, formal and that follows purely scientific techniques. The translator therefore should be skillful, having professional know-how in order to construct the target discourse in a successful and comprehendible way, despite that fact that the dentiststranslators themselves have adequate experience of the subject matter of the text typology they embark on. Yet they, to some extent, could scarcely render SL into the suitable construction on TL discourse and that could be due to the lack of the contrastive discoursal structures between English and Arabic in order to realize a more successful rendering in the target language.